Morphostructural Characters of a Recently Rescued Goat Breed - Parés-Casanova, P.M. (2015)
Quantitative characters based on 19 morphostructural variables from 23 adult females of the newly recovered «Cabra Catalana» goat were studied. The sample corresponded to animals located in the same foundational herd in Catalunya, NE Spain. Studied animals presented medium homogeneity and low harmony degrees. It is suggested that breed standards must be prepared in order to officially recognize this population.